HUBUNGAN LINGKUNGAN FISIK RUMAH DENGAN KEJADIAN TUBERCULOSIS PARU - Lestiyaningsih, Tuti (Poltekkes Kemenkes Tanjung Karang, 2020)
Tuberculosis is an infectious disease caused by the bacteria Mycobacterium tuberculosis. Data from the Tanjung Sari Health Center in South Lampung Regency shows that there has been an increase in cases in the last two years, 46 cases in 2015 and 47 cases in 2016. Until the end of semester 1 of 2017, an additional 33 cases were recorded. This study aims to determine the relationship between sex and the physical environment of the house with the incidence of pulmonary tuberculosis at Tanjung Sari Public Health Center.This study used an analytic survey method with a case-control design. The population is people who are registered as patients of Tanjung Sari Public Health Center, from January to June 2017. The sample is 74 people, consisting of 37 cases and 37 controls.Â The results showed that women predominantly suffer from pulmonary tuberculosis. The physical environment includes the area of ventilation, the presence of cross-ventilation, and the position of the window as risk factors for pulmonary TB disease. It is recommended that people get used to opening windows to maintain the availability of fresh air in the room and the entry of sunlight. Puskesmas should increase the capacity of cadres in providing knowledge on the prevention of pulmonary tuberculosis to the community.